Penanaman Budaya Kemaritiman pada Pendidikan Non Formal (Paud-TK) sebagai Upaya Peningkatan Kesadaran Indonesia Sebagai Bangsa Maritim untuk Perkembangan Sektor Maritim Berkelanjutan Kedepannya - Silma Nurisshobakh; Resindra Prameswari; Lutfi Prasetyo Utomo; Denny Oktavina Radianto (International Consortium of Education and Culture Research Studies, 2018)
Maritime State is a country situated in the territorial sea, has many islands, surrounded by the sea and the waters of the region, and most of the inhabitants work in the territorial waters. Indonesia as a Maritime State has been recognized by the world through UNCLOS 1982, this recognition was later ratified by Act No. 17 of the year 1985. The importance of instilling a culture of the Musée on early education is as the formation of the character and mindset of a child as a person who dares to take risks like a sailor who must always think to take risks when in the sea. So when an adult later Indonesia children grow into the next generation of the nation dared to take risks, are accustomed to critical thinking, understanding nature around, so hopefully can explore nature Indonesia so that useful and beneficial for the existence of the nation and the State of the next article. By applying the leading culture began early expected later the younger generation grow up to be a generation that can explore and exploit nature Indonesia especially Indonesia sea that hold tremendous wealth that can be beneficial for nation in sustainability in the future.